Peran Syeikh dalam Pembentukan Karakter Generasi Ranah Minangkabau Sumatera Barat di Lembaga Pendidikan Surau - Yusutria, Yusutria (Journal of Islamic Education, 2021)
A good nation is a nation that has a character that is manifested in thoughts, feelings, attitudes, behaviors, and configurations that are based on religious, legal, customary, religious, and cultural values. Not a drug addict, which will damage the morals of religion and culture. To realize a generation of character, the role of the Syeikh is needed in the formation of the character of the generation of the Minangkabau realm of West Sumatra in the Surau educational institution. The purpose of the study is to study the character shape of students, the role of the Syeikh in character formation. As a result of research, research is conducted by collecting data through interviews, observation, documentation. While the forms of character instilled religious values, discipline, honesty, independence is hard work full of creativity, curiosity with the full sense of responsibility. Sheikh managed to become a good character, instilling good and responsible habits, encouraging and innovating.